2015
DOI: 10.1093/mnras/stu2579
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical constraints on the origin of timing signals from black holes

Abstract: We present a systematic study of the orbital inclination effects on black-hole transients fast time-variability properties. We have considered all the black-hole binaries that have been densely monitored by the Rossi XTE satellite. We find that the amplitude of low-frequency quasi periodic oscillations (QPOs) depends on the orbital inclination. Type-C QPOs are stronger for nearly edge-on systems (high inclination), while type-B QPOs are stronger when the accretion disk is closer to face-on (low inclination). O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
249
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(266 citation statements)
references
References 103 publications
(118 reference statements)
16
249
1
Order By: Relevance
“…Type-C QPOs, on the other hand, mostly occur in the intermediate and hard states at frequencies between 0.1 Hz and 30 Hz, in reasonably good agreement with the QPOs observed here at 73 mHz, 136 mHz, and 1.03 Hz. Additionally, given V404 Cygni's orbital inclination of  -+ 67 1 3 (Shahbaz et al 1994;Khargharia et al 2010), it follows the general trend of Type-C QPOs in high-inclination systems to have higher fractional rms amplitudes (Heil et al 2015;Motta et al 2015b), though unlike most Type-C QPOs, these QPOs are likely highly transient.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Type-C QPOs, on the other hand, mostly occur in the intermediate and hard states at frequencies between 0.1 Hz and 30 Hz, in reasonably good agreement with the QPOs observed here at 73 mHz, 136 mHz, and 1.03 Hz. Additionally, given V404 Cygni's orbital inclination of  -+ 67 1 3 (Shahbaz et al 1994;Khargharia et al 2010), it follows the general trend of Type-C QPOs in high-inclination systems to have higher fractional rms amplitudes (Heil et al 2015;Motta et al 2015b), though unlike most Type-C QPOs, these QPOs are likely highly transient.…”
Section: Discussionmentioning
confidence: 72%
“…Among the phenomenology of QPOs in BHXBs, generally two classes can be distinguished: high-frequency QPOs (HFQPOs) in the range of 100-500 Hz (e.g., Remillard et al 1999aRemillard et al , 1999bMiller et al 2001;Strohmayer 2001) and LFQPOs between 0.05 and 30 Hz (Motch et al 1983;Miyamoto & Kitamoto 1991;Takizawa et al 1997;Motta et al 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Type-B QPOs have been associated to the relativistic jets usually seen in X-ray binaries (Fender et al, 2009) in transition from hard to soft state. Motta et al, 2015 has shown that the intrinsic power of type-B QPOs is higher for low inclination sources (i.e. for sources where the angle between the line of sight and the accretion disk axis is small).…”
Section: Type-b Qposmentioning
confidence: 99%
“…2, bottom panel and Fig. 1) are characterized by a strong (up to 20% rms), narrow (ν/∆ν ≥10) and variable peak (its centroid frequency and intensity varying by several percent in a few days; see, e.g., Motta et al, 2015) superposed on a flat-top noise that steepens above a frequency comparable to the QPO frequency. A subharmonic, a second harmonic peak are often seen and sometimes even a third harmonic peak.…”
Section: Type-b Qposmentioning
confidence: 99%
“…4, Some of type-B QPO in Motta et al (2015) are inconclusive for us which makes it hard to put them into standard type-B QPO class. Although they are surly not type C or type A QPO, by comparing to other normal type-B QPOs, they are remarkably distinguished by their band-limit noise shapes.…”
Section: The Samplementioning
confidence: 99%